The Integration of Digital Technology in Public Management Transformation: : Implications for Educational Advancements in Indonesia - Sumarno Sumarno (International Journal of Asian Education, 2023)
The study aims to explore how integrating digital tools and platforms in public management practices can enhance educational outcomes and address the challenges faced by the Indonesian education system. The research methodology employs a qualitative approach, including interviews with key stakeholders, document analysis, and case studies. The results indicate that digital technology can revolutionize teaching and learning methods, promote student engagement, and facilitate access to quality educational resources. However, infrastructure gaps, teacher training, and equitable access to technology remain key concerns. The implications of this study emphasize the need for strategic planning, policy development, and investment in digital infrastructure and teacher professional development programs to effectively leverage digital technology in transforming public management and advancing education in Indonesia.